SIMULATION OF INJECTION WELL IMPLEMENTATION TO OVERCOME SEA WATER INTRUSION IN NORTH JAKARTA WITH VARIATION OF INJECTION RATE, AMOUNT OF WELL AND RECHARGE TIME - Eka Putri, Arditari
Ground water used as main source of raw water for most people. Problem that arise is the occurrence of sea water intrusion in North Jakarta decreases ground water quality. The solution offered to overcome intrusion is the use of injection wells. However application in the field is constrained by the optimal number, rate of injection and location of wells related to the cost and effectiveness of injection wells. The aim of this study is to model current condition of sea water intrusion, simulate the application of injection wells to overcome intrusion with variables: location, injection rate, number of well and how long injection should be done for unconfined and upper confined aquifer. The research sites cover Jakarta Groundwater Basin area. Modeling was done first by simulating groundwater flow using MODFLOW under steady state, followed by intrusion modeling using SEAWAT. After obtaining the appropriate intrusion model, the application of injection wells is modeled. Variations were made among location of injection wells, recharge rates, number of wells with a simulation time of 10 years. After obtaining optimal results, the recharge time is varied again so that a significant change in the area of intrusion is found.